2014
DOI: 10.1111/ijfs.12680
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of antioxidant and nitric oxide inhibitory peptides from Tilapia (Oreochromis niloticus) protein hydrolysate

Abstract: Nitric oxide (NO)-inhibitory and antioxidative activities of tilapia hydrolysates were prepared using ultrasound pretreatment at 70 W for 30 and 45 min, respectively, followed by Flavourzyme hydrolysis for 1 h. Both hydrolysates were fractionated using size exclusion chromatography on Sephadex G-25 column and purified by RP-HPLC. The amino acid sequence of the most potent and purified fractions was determined using LC/MS/MS. The antioxidant peptide (KAFAVIDQDKSGFIEEDELKLFLQNFSAGARAGDSDG DGKIGVDEFAALVK, MW: 633… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Various types of methods have been used to evaluate the antioxidant activity of fish-derived peptides, including the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging assay, hydroxyl radical scavenging activity, Cu 2+ chelating activity, and Fe 2+ chelating activity [ 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Marine Fish-derived Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of methods have been used to evaluate the antioxidant activity of fish-derived peptides, including the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging assay, hydroxyl radical scavenging activity, Cu 2+ chelating activity, and Fe 2+ chelating activity [ 99 , 100 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Marine Fish-derived Peptidesmentioning
confidence: 99%
“…They are currently extensively studied in the development of cosmeceutical products, including lotions, shampoos, and moisture creams. Numerous studies have reported that marine fish-derived peptides can be used as antimicrobial agents, as shown in Table 5 [ 103 , 104 , 105 , 106 ]. The enzymes used for the isolation of antimicrobial fish peptides and the microorganisms susceptible to these antimicrobial peptides were listed in Table 5 .…”
Section: Marine Fish-derived Peptidesmentioning
confidence: 99%
“…Fish protein hydrolysates have also demonstrated both anti-inflammatory activity [10][11][12][13][14][15] and proinflammatory activity [16,17] via modulation of nitric oxide (NO) and inflammatory cytokines such an interleukin (IL)-6 and tumour necrosis factor-alpha (TNF-α) in macrophage cell lines. The use of macrophage cells has become an increasingly popular approach to investigate the antioxidant potential of natural bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of L‐arginine to L‐citrulline is one of the proper methods for production of NO radical. Excessive production of this radical significantly increases the risk of various types of cancer, atherosclerosis, chronic inflammation, and rheumatoid arthritis (Kangsanant et al., 2015). In this study, the effects of the type of enzyme and pollen protein on NO free radical inhibition were studied (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%